Racial, ethnic and social discrimination in Peru. A critical assessment of recent empirical research - Santos, Martín (2014)
There is a growing interest in studying discrimination in Peruvian Social Science. Against this backdrop, this article seeks to assess critically recent empirical research on discrimination in Peru, with an emphasis on racial, ethnic and social discrimination in employment and income, firms, health organizations, education, relationship with public agencies and everyday life. After reviewing the relevant literature on discrimination, this article presents a critical appraisal, taking into consideration the research questions posed, the theoretical frameworks and analytical categories used, the ways in which the notion of «race» is measured, the questions asked to measure discrimination, the manners in which discrimination is detected, and the (debatable) ways researchers interpret their findings. The articleconcludes by highlighting gaps in the literature which should be addressed.